Violent Victimization as a Risk Factor for Violent Juvenile Behavior - Stevković, Ljiljana (Zbornik Instituta za kriminološka i sociološka istraživanja, 2007)
Violence presents a reality of every social system and has its manifestation at personal and family, as well as at broader social and global levels. In the family that is supposed to represent a safe and loving oasis, a child could be directly or indirectly victimised by violence. Besides individual, family violence produces negative social consequences as a result of the delinquent conduct of the victimised child. This paper was based on the idea of the existence of risk factors for violent criminal conduct. On the basis of brief analyses of theoretical explanations and empirical results, the relation between previous exposure to family violence and later violent criminal conduct of juveniles was pointed out. Earlier onset, more likelihood development of a violent criminal career. Accordingly, the need for systematic exploration of violent juvenile crime, with special emphasis on the relation with previous violent victimisation, in order to early detection and intervention was emphasised.